Caldas Novas (GO): turismo e fragmentação sócio-espacial (1970-2005) - Borges, Olinda Mendes (2005)
This work has for objective to understand the political, economical and social processes that influence the construction of the urban space of Caldas Novas (GO). The paradisiacal image impels, in the present time, the leisure tourism, with the exploration of is thermal waters. A symbolic space reinforces the political speech of the largest tourist pole of Goiás and materializes the city that increases at any price. The tourism, at the same time that open job vacance, segregate the ugly side of the city: the poor and their precarious houses. The tourism slash the city and submit it to speculation. To prepare the city for the tourist imposed to Caldas Novas architectural and urban pattern that accentuated the differences, reinforcing the characteristics of a segregated and fragmented city.